2019
DOI: 10.1055/s-0039-1692478
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30-Day Non-Neurological Morbidity and Cerebrospinal Fluid Leak in Patients Undergoing Surgery for Vestibular Schwannoma

Abstract: Introduction We analyzed perioperative risk factors for morbidity and mortality for the patients undergoing surgical intervention for vestibular schwannoma along with rates of cerebrospinal fluid (CSF) leaks that required surgery. Materials and Methods Patients undergoing surgery vestibular schwannoma were identified in the American College of Surgeons National Surgical Quality Improvement Program database from 2012 to 2016 using current procedural terminology (CPT) codes for posterior fossa surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Our study highlights the economic implications of CSF leak following VS surgery over the long term. Our results are concordant with another national database study which reported a 3.7% incidence of CSF leak following VS resection and 56.3% required surgical repair for CSF leak [3].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study highlights the economic implications of CSF leak following VS surgery over the long term. Our results are concordant with another national database study which reported a 3.7% incidence of CSF leak following VS resection and 56.3% required surgical repair for CSF leak [3].…”
Section: Discussionsupporting
confidence: 92%
“…Cerebrospinal fluid (CSF) leak following vestibular schwannoma (VS) surgery can occur in up to 13% of patients [1][2][3]. Types of surgical approaches [(translabyrinthine, TL up to 13%), (middle fossa, MF and retrosigmoid, RS up to 10.6% each)] have not been shown to have an impact on the incidence of CSF leak [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors have been inconsistently associated with increased CSF leak risk after lateral skull base surgery—BMI, male gender, tumor size, functional status, combined approaches, or length of surgery. 10,22-27 Most of the patients in our scoping review were female—in both failed and revision subsets. BMI was only reported in our retrospective series and averaged 23.9 kg/m 2 (SD ± 4.9).…”
Section: Discussionmentioning
confidence: 99%